2014
DOI: 10.1155/2014/584957
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Surgery for Rare Cases of Anterior Urethral Metastasis in Prostate Cancer

Abstract: Penis metastasis from prostate cancer is very rare, and its management varies from case to case as there are very few cases reported in the literature. We describe a patient with prostate cancer treated with radiotherapy and androgen deprivation therapy who presented with urethral bleeding as a symptom of anterior urethral metastasis during followup. We propose a way to manage this and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…They also reported that 41% of patients had died of cancer within 6 months after diagnosis 12 . However, to the best of our knowledge, patients with urethral metastasis from prostate cancer that have been reported since 2000 had better prognosis: only two patients died within 2 years after diagnosis 1–9 . Compared with penile metastasis, urethral metastasis is more likely to cause hematuria and lower urinary tract symptoms, which may lead to early detection and treatment.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They also reported that 41% of patients had died of cancer within 6 months after diagnosis 12 . However, to the best of our knowledge, patients with urethral metastasis from prostate cancer that have been reported since 2000 had better prognosis: only two patients died within 2 years after diagnosis 1–9 . Compared with penile metastasis, urethral metastasis is more likely to cause hematuria and lower urinary tract symptoms, which may lead to early detection and treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment of metastatic prostate cancer to the urethra remains controversial. Most patients underwent ADT with or without transurethral resection, 2,3,6–9 and some cases of prostate cancer metastasizing to the urethra during ADT were treated with chemotherapy 1,4 . Cases of recurrent urethral tumors after achieving remission with ADT have been also reported, and urethrectomy and CyberKnife radiotherapy were performed with good outcomes 3,6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations